(untitled) (Teología, 2018)
The danger of understanding the ways of reform proposed by Pope Francis as a “make-up” of antiquated structures stems from the laziness, that can arise from having to deepen the review of our categorizations and systemic organizations. This article wants to offer a bouquet of ideas to collaborate with the reflection on the models with which we approach the organization of our theological languages.